Chemical Characterization of Cumin Seed Oil (Cuminum Cyminum) by Gcms and its Comparative Study - Gotmare, S. R.; Tambe, E. A. (International Journal of Scientific Research in Biological Sciences, 2018)
Cumin (Cuminum cyminum L.) is among the large number of spices used to flavour food and beverages. In this study the chemical composition of the extracted cumin seed oil and market cumin oil were analysed by GCMS and compared. The comparative study revealed that there is a huge difference between these two oils. The extracted cumin oil was found rich in oxygenated terpenoids. In addition to this, a comparative study from the data of chemical composition of cumin seeds from different countries also showed variation in the chemical components depending upon the geography, environment, climate, harvesting stage, etc.